Rancang Bangun UI/UX Aplikasi Pemesanan Makanan “JoSsy” Berbasis Mobile dengan Design Thinking dan Evaluasi System Usability Scale (SUS) - Wijaya, Jonathan Briant; Lianawati, Yosita; Widiastuti, Rosalina Yani; Wibowo, Adhi (Journal of Entrepreneurship & Technopreneurship, 2026)
The rapid growth of online food ordering services requires UI/UX designs that are easy to learn, efficient, and consistent—especially at high-value user journeys such as checkout and payment. This study aims to design the UI/UX of a mobile-based food ordering and delivery application, JoSsy, using the Design Thinking approach consisting of Empathize, Define, Ideate, Prototype, and Testing. The design process produced a structured user flow, wireframes, and a high-fidelity interactive prototype built in Figma, covering key features including login, menu browsing/selection, cart, checkout, payment, and delivery tracking. Usability was evaluated using the System Usability Scale (SUS) to obtain a quantitative measure of user acceptance. Based on an initial pilot (n=10) using sample/pilot data, the prototype achieved an average SUS score of 84.75, categorized as Acceptable, indicating that the proposed UI/UX is well-received and suitable as a foundation for further implementation and development.